(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The problem of preventing the negative impact of man-made environmental pollution on human health and environmental components is becoming most urgent. Emissions of pollutants into the atmosphere have a negative impact on all components of the environment, primarily on atmospheric air, soil, and human health. South Kyrgyz Cement Closed Joint Stock Company is one of the sources of environmental pollution in the south of Kyrgyzstan. The purpose of the study is to study the environmental problems of the impact of an industrial enterprise on the environment. The general description of the main sources of pollutants of atmospheric air by the enterprise, the composition of pollutants and the effect of these substances on the human body is given.